Analysis of Series Hybrid Electric Vehicle with Auxiliary Power Unit (Global Journals of Research in Engineering, 2013)
Hybrid electric vehicles represent a promising future direction for the transportation sector in terms of decreasing the reliance on fossil fuels while simultaneously decreasing emissions. Energy used for driving is fully or partially shifted to electricity leading to lower emission rates.In this regard, the use of a power generator and motor as the primary power source for an automobile is very attractive. This thesis develops model of a series hybrid vehicle with a power generator as its Auxiliary Power Unit (APU). Simulation using the model helps to provide an understanding of the interaction and flow of power. Moreover, electrical power sharing between the APU and the Electrical Storage System (ESS) is shown. Conclusion is also discussed.
Keywords: traction motor; control strategy; tractive effort etc